انواع تقرير مراجع الحسابات - فلة, بالحشاني; هيفاء, بوصبيع صالح; فاطمة الزهراء, بوقطاية (جامعة الوادي - University of Eloued, 2023)
يعتبر التقرير هو وسيلة المرجع مدقق الحسابات لتلخيص ما تم انجازه من عملية المراجعة تدفق الحسابات حيث يمثل المرحلة التي تعرض فيها مشكلات او الانحرافات ثم التوصيات والاقتراحات الاتي يرى المراجع مدقق الحسابات وجرب تنفيذها وهو ايضا الوسيلة الرئيسية التي تربط المراجع مدقق الحسابات مع جميع الاطراف المستفيدة منه ولذلك لا بد من اخذ الحيطة والحذر في اعداد وكتابة تقرير The report is the reference auditor’s way to summarize what has been accomplished in the audit process, the flow of accounts, as it represents the stage in which problems or deviations are presented, and then the recommendations and suggestions that the auditor sees and tries to implement. It is also the main means that connects the auditor with all the parties benefiting from it. Therefore Care must be taken in preparing and writing a report
Keywords: انواع التقرير، مراجع الحسابات، المراجعة; Types of report, auditor, audit